Pupil size affects measures of eye position in video eye tracking: implications for recording vergence accuracy - Wolfgang Jaschinski (Bern Open Publishing, 2016)
Video eye trackers rely on the position of the pupil centre. However, the pupil centre can shift when the pupil size changes. This pupillary artifact is investigated for binocular vergence accuracy (i.e. fixation disparity) in near vision where the pupil is smaller in the binocular test phase than in the monocular calibration. A regression between recordings of pupil size and fixation disparity allows correcting the pupillary artefact. This corrected fixation disparity appeared to be favourable with respect to reliability and validity, i. e. the correlation of fixation disparity versus heterophoria. The findings provide a quantitative estimation of the pupillary artefact on measured eye position as function of viewing distance and luminance, both for measures of monocular and binocular eye position.